Pass-through of temporary fuel tax reductions: Evidence from Europe - Chiara Drolsbach; Maximilian Maurice Gail; Phil-Adrian Klotz (Philipps-University Marburg, School of Business and Economics, 2022)
Several European countries have implemented temporarily fuel tax reductions in 2022 to relieve the financial burden on their citizens. This paper provides estimates of the pass-through rates as well as the effect on retail margins for France, Germany and Italy. Using a unique data set containing daily consumer prices for gasoline and diesel in five European countries, we employ a staggered Difference-in-Differences design. Our results show a very heterogeneous pass-through of the fuel tax reductions depending on the country and on the type of fuel. These findings also have important implications for the effective design of unconventional fiscal policy as well as for competition policy in the fuel market.
Keywords: 330; pass-through; fuel taxes; staggered DiD